Transforming Bangladesh's Agri-Food Systems: Workshop on Inclusive Governance for Climate Resilience - Bangladesh Agricultural Research Council (2024)
This report documents the results of the workshop on Transforming Bangladesh's Agri-Food Systems: Workshop on Inclusive Governance for Climate Resilience. The workshop aimed to bring together key stakeholders and initiate the co-development of an inclusive food systems governance framework focusing on the Southwestern deltaic part of Bangladesh. The workshop outcome was to identify actionable pathways to climate resilient food systems that prioritize food and livelihood security of the most marginalized in the face of escalating climate risks. This event was organized by the Bangladesh Agricultural Research Council, with support from the CGIAR Initiative on Asian Mega-Deltas.